Mn2Ga2S5 and Mn2Al2Se5 van der Waals Chalcogenides: A Source of Atomically Thin Nanomaterials - Ivan V. Chernoukhov; Alexey V. Bogach; Kirill A. Cherednichenko; Ruslan A. Gashigullin; Andrei V. Shevelkov; Valeriy Yu. Verchenko (Molecules, 2024)
Layered chalcogenides containing 3d transition metals are promising for the development of two-dimensional nanomaterials with interesting magnetic properties. Both mechanical and solution-based exfoliation of atomically thin layers is possible due to the low-energy van der Waals bonds. In this paper, we present the synthesis and crystal structures of the Mn2Ga2S5 and Mn2Al2Se5 layered chalcogenides. For Mn2Ga2S5, we report magnetic properties, as well as the exfoliation of nanofilms and nanoscrolls. The synthesis of both polycrystalline phases and single crystals is described, and their chemical stability in air is studied. Crystal structures are probed via powder X-ray diffraction and high-resolution transmission electron microscopy. The new compound Mn2Al2Se5 is isomorphous with Mn2Ga2S5 crystallizing in the Mg2Al2Se5 structure type. The crystal structure is built by the ABCBCA sequence of hexagonal close-packing layers of chalcogen atoms, where Mn2+ and Al3+/Ga3+ species preferentially occupy octahedral and tetrahedral voids, respectively. Mn2Ga2S5 exhibits an antiferromagnetic-like transition at 13 K accompanied by the ferromagnetic hysteresis of magnetization. Significant frustration of the magnetic system may yield spin-glass behavior at low temperatures. The exfoliation of Mn2Ga2S5 layers was performed in a non-polar solvent. Nanolayers and nanoscrolls were observed using high-resolution transmission electron microscopy. Fragments of micron-sized crystallites with a thickness of 70–100 nanometers were deposited on a glass surface, as evidenced by atomic force microscopy.